2016
DOI: 10.1371/journal.pone.0161712
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Adherence to Non-Pharmacological Guidelines for Hypertension

Abstract: This study aimed to compare levels of adherence to non-pharmacological guidelines between patients with and without hypertension diagnoses, and examined temporal changes in adherence during recent decades. We used data from the Korean National Health and Nutrition Examination Survey (1998–2012), including 13,768 Korean hypertensive patients aged ≥ 30 years who were categorized according to the presence or absence of a hypertension diagnosis, based on blood pressure and self-reported information. Adherence to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…However, guidelines for lifestyle modification are not widely followed [11][12][13]. Despite the well-known benefits of dietary intervention, compliance with dietary guidelines for hypertension is poorest for health-related behaviors such as non-smoking, alcohol consumption in moderation, and physical activity [13,14], and unhealthy diet has been reported to be a major barrier to disease management [15]. Several studies have been conducted to gain insight into the knowledge and disease management practices of individuals with hypertension and/or diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…However, guidelines for lifestyle modification are not widely followed [11][12][13]. Despite the well-known benefits of dietary intervention, compliance with dietary guidelines for hypertension is poorest for health-related behaviors such as non-smoking, alcohol consumption in moderation, and physical activity [13,14], and unhealthy diet has been reported to be a major barrier to disease management [15]. Several studies have been conducted to gain insight into the knowledge and disease management practices of individuals with hypertension and/or diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…A similar finding was reported in Malaysia were complying with low salt and low-fat diet was difficult due to the lack of family and peer support. 37 The challenge of adapting a salt-free diet was also reported by another study. 38 …”
Section: Discussionmentioning
confidence: 69%
“…According to the data obtained by "The Seventh Report of the Joint National Committee on Prevention, Detection, Evaluation, and Treatment of High Blood Pressure" suggesting that only one third of hypertensive patients had well controlled blood pressure (5), at least a part of this problem could have been assigned to the low adherence to healthy lifestyle. Study conducted in Poland also proved that implementation of non-pharmacological treatment among hypertensive patients is at very (12). Recent study showed that the intensive antihypertensive medical treatment combined with the lifestyle modification led to the better blood pressure control of hypertensive patients including the elderly (10).…”
Section: Discussionmentioning
confidence: 99%
“…The results of our study demonstrated that only a third to no less than a half of hypertensive patients has been advised by their physician about the appropriate diet, physical activity and smoking cessation that were an obligatory part of a treatment. In addition, the counseling by the other health workers including pharmacists also plays an important role in medical adherence as well as in the adherence to lifestyle behavior (12,13). Among the reasons for the low counseling rates by physicians could be assigned to their poor and/or inadequate knowledge regarding the hypertension and hypertension guidelines (14) and the short period of time allowed for the physician-patient encounter since the proper physicians counseling required more time (15,16).…”
Section: Discussionmentioning
confidence: 99%